Formative Feedback Quality, Self-Efficacy, Competency Achievement, and Work Readiness in Vocational Schools: SEM-PLS - Wirda Yetti; Hasan Maksum; Ambiyar Ambiyar (Juwara: Jurnal Wawasan dan Aksara, 2026)
This research examined the direct and indirect relationships among formative feedback quality, student self-efficacy, competency achievement, and work readiness in a non-urban vocational school context. A quantitative explanatory design was employed involving all 150 students at SMKN 1 Simpang Alahan Mati, Pasaman, West Sumatra, through total sampling. Data were collected using validated five-point Likert-scale questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. All constructs met convergent validity, composite reliability, and discriminant validity thresholds. Results confirmed that formative feedback quality significantly affected student self-efficacy, competency achievement, and work readiness, while student self-efficacy demonstrated the strongest predictive effect on competency achievement with a large effect size and significantly influenced work readiness, thus accepting all five hypotheses. Mediation analysis confirmed that student self-efficacy partially mediates the relationship between formative feedback quality and both vocational outcome variables, establishing that feedback influences outcomes through concurrent direct instructional and indirect psychological mechanisms. These findings demonstrate that the gap between vocational education outcomes and workforce requirements in non-urban schools is substantially explained by the combined insufficiency of formative feedback quality and student self-efficacy, and that addressing graduate workforce readiness requires coordinated investment in both dimensions simultaneously.